X-Ray Fine Structure of a Limb Solar Flare Revealed by Insight-HXMT, RHESSI and Fermi. (1st May 2022) - Zhang, Ping; Wang, Wei; Su, Yang; Zhang, Shuangnan; Song, Liming; Lu, Fangjun; Zhang, Shu
Abstract: We conduct a detailed analysis of an M1.3 limb flare occurring on 2017 July 3, which have the X-ray observations recorded by multiple hard X-ray telescopes, including Hard X-ray Modulation Telescope (Insight-HXMT), Ramaty High Energy Solar Spectroscopic Imager (RHESSI), and the Fermi Gamma-ray Space Telescope (Fermi). Joint analysis has also used the extreme ultraviolet (EUV) imaging data from the Atmospheric Imaging Assembly (AIA) aboard the Solar Dynamic Observatory. The hard X-ray spectral and imaging evolution suggest a lower corona source, and the non-thermal broken power law distribution has a rather low break energy ∼15 keV. The EUV imaging shows a rather stable plasma configuration before the hard X-ray peak phase, and accompanied by a filament eruption during the hard X-ray flare peak phase. Hard X-ray image reconstruction from RHESSI data only shows one foot point source. We also determined the DEM for the peak phase by SDO/AIA data. The integrated EM beyond 10 MK at foot point onset after the peak phase, while the >10 MK source around reconnection site began to fade. The evolution of EM and hard X-ray source supports lower corona plasma heating after non-thermal energy dissipation. The combination of hard X-ray spectra and images during the limb flare provides the understanding on the interchange of non-thermal and thermal energies, and relation between lower corona heating and the upper corona instability.